Myeloma - the integral role played by the professional nurse - Lucille Wood (AOSIS, 1989)
Myeloma is a malignancy o f plasma cells which are terminally differentiated B-lymphocytes. The diagnosis may he made incidentally at routine blood testing, when an abnormality is found in the plasma proteins on electrophoresis. More usually the patients are symptomatic, with bone pain, anaemia, evidence o f renal failure, or the metabolic abnormalities associated with increased plasma calcium and urate levels. Effective treatment will extend survival from 7 to approximately 30 months and at the same time improve the quality o f life. Treatment is multidisciplinary, prominently involves the professional nurse and may arbitrarily be divided into two stages. Firstly, reversible lesions, such as dehydration and plasma hyperviscosity must be corrected, hypercalcaemia and hyperuricaemia improved and, if necessary, renal dialysis undertaken. Secondly, but o f equal importance, is the need for specific therapy to be directed against the tumour itself, and both cytotoxic agents and irradiation have an important role to play. More recently, newer approaches have included high dose chemotherapy and bone marrow transplantation.